Meta-analysis of use of balloon pulmonary angioplasty in patients with inoperable chronic thromboembolic pulmonary hypertension. (15th September 2019) - Khan, Muhammad Shahzeb; Amin, Emaan; Memon, Muhammad Mustafa; Yamani, Naser; Siddiqi, Tariq Jamal; Khan, Safi U.; Murad, Mohammad Hassan; Mookadam, Farouk; Figueredo, Vincent M.; Doukky, Rami; Benza, Raymond L.; Krasuski, Richard A.
Abstract: Background: Current guidelines give balloon pulmonary angioplasty (BPA) a Class IIb recommendation for use in inoperable chronic thromboembolic pulmonary hypertension (CTEPH), as its safety and efficacy remain poorly defined. We conducted a systematic review and meta-analysis to evaluate BPA effectiveness. Methods: Medline, Cochrane Library and Scopus were searched for original studies from database inception dates until 24th May 2018. Prospective studies reporting outcomes before and after BPA in inoperable CTEPH patients were included. Studies with <20 patients were excluded. Data were pooled using a random effects model represented as weighted mean differences with 95% confidence intervals (CIs). Results: Seventeen noncomparative studies comprising 670 CTEPH patients (mean age 62 years; 68% women) were included. Meta-analysis showed significantly decreased mean pulmonary artery pressure (−14.2 mm Hg [95% CI −18.9, −9.5]), pulmonary vascular resistance (−303.5 dyn·s/cm 5 [95% CI −377.6, −229.4]) and mean right atrial pressure (−2.7 mm Hg [95% CI −4.1, −1.3]) after BPA. Six-minute walk distance (67.3 m [95% CI 53.8, 80.8]) and cardiac output (0.2 l/min [95% CI 0.0, 0.3]) were significantly increased following BPA. From 12 studies reporting mortality with median follow-up of 9 months after BPA (range, 1–51 months), pooled incidence of short (≤1 month) and long-term mortality (>1 month) was 1.9% and 5.7%, respectively. Conclusion: This systematic review and meta-analysis suggests mildly improved hemodynamics and overall low mortality rates following BPA in inoperable CTEPH patients. This non-comparative evidence can be used to facilitate decision making until the results of larger, controlled studies become available. Highlights: Balloon pulmonary angioplasty (BPA) is a relatively safe procedure. Significant hemodynamic improvements observed after BPA. Reperfusion lung injury and reperfusion edema are common complications after BPA.